Assessment of the relationship between generalized convulsive epilepsy and systemic inflammatory regulators: a bidirectional Mendelian randomization study - Wang, Shengnan; Su, Tengfei; Pang, Shuyan; Wang, Jianglong; Lang, Yue; Zhu, Mingqin; Cui, Li (Frontiers in Neurology, 2023)
Background Generalized convulsive epilepsy (GCE), an important subtype of epilepsy, is a syndrome of neuronal dysfunction characterized by diffuse abnormal discharge of neurons within the brain. Compounding evidence suggests a correlation between epilepsy and inflammatory factors, for instance, cyclooxygenase-2, interleukin-1β, and interleukin-6. Elevated levels of inflammatory factors have been observed in patients with epilepsy and several animal models. Therefore, inflammation may be closely associated with the pathogenesis and progression of GCE. However, the cause-and-effect relationship between the two is difficult to determine because of small sample sizes and confounding factors. Methods To test for causality of the 41 cytokines on GCE, we conducted a two-sample Mendelian randomization (MR) based on the largest and latest genome-wide association study (GWAS) involving 290 cases and 453,521 European controls and a GWAS meta-analysis consisting of 41 cytokines from 8,293 individuals. Results R confirmed a bidirectional causal link between cytokines and GCE. Genetically predicted increased levels of hepatocyte growth factor and decreased levels of eotaxin and interleukin-18 are associated with an increased risk of GCE (OR = 1.904, 95% CI = 1.019–3.561, p = 0.044; OR = 0.641, 95% CI = 0.417–0.984, p = 0.042; OR = 0.482, 95% CI = 0.251–0.927, p = 0.046). Furthermore, the presence of GCE is related to an increase in levels of multiple cytokines, such as macrophage inflammatory protein-1α, interleukin-12p70, interleukin-17, interleukin-1 receptor antagonist, and basic fibroblast growth factor (OR = 1.038, 95% CI = 1.005–1.073, p = 0.024; OR = 1.031, 95% CI = 1.009–1.054, p = 0.006; OR = 1.027, 95% CI = 1.002–1.053, p = 0.037; OR = 1.037, 95% CI = 1.003–1.072, p = 0.032; OR = 1.032, 95% CI = 1.000–1.066, p = 0.048; OR = 1.025, 95% CI = 1.003–1.048, p = 0026). Conclusion A bidirectional causal link existed between inflammation and GCE. Detecting significantly altered factor concentrations may be of great significance for screening GCE and predicting their occurrence. Moreover, available pharmacological treatments for GCE are focused primarily on suppressing seizures. In future, altering the concentration of these cytokines in the body through targeted anti-inflammatory therapy to modify the epileptogenic mechanism and prevent the recurrence and refractoriness of GCE may become the key to new treatments.